2010
DOI: 10.1111/j.1365-2605.2010.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary antioxidants improve arteriogenic erectile dysfunction

Abstract: Most cases of erectile dysfunction (ED) are associated with oxidative stress risk factors such as diabetes mellitus, smoking, hypercholesterolaemia and hypertension. Our goal was to search for markers of oxidative stress in arteriogenic ED and examine the protective role of dietary antioxidants. Atherosclerosis-induced ED was developed in rabbits by balloon de-endothelialization of the iliac arteries. Ballooned and age-matched control animals were assigned into subgroups receiving pomegranate extract antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 34 publications
0
45
0
2
Order By: Relevance
“…Estas desregulações moleculares podem afetar a estrutura celular do CC, induzindo por sua vez alterações deletérias nos mecanismos de vasorelaxamento [5][6][7] . De facto, surgem cada vez mais evidências que reforçam o papel central do stresse oxidativo na etiologia da DE diabética 9,10,18,19 . No entanto, os estudos de investigação básica centraram-se particularmente na avaliação da produção de ERO e no efeito da administração de antioxidantes 7,9,10,18,19 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estas desregulações moleculares podem afetar a estrutura celular do CC, induzindo por sua vez alterações deletérias nos mecanismos de vasorelaxamento [5][6][7] . De facto, surgem cada vez mais evidências que reforçam o papel central do stresse oxidativo na etiologia da DE diabética 9,10,18,19 . No entanto, os estudos de investigação básica centraram-se particularmente na avaliação da produção de ERO e no efeito da administração de antioxidantes 7,9,10,18,19 .…”
Section: Discussionunclassified
“…De facto, surgem cada vez mais evidências que reforçam o papel central do stresse oxidativo na etiologia da DE diabética 9,10,18,19 . No entanto, os estudos de investigação básica centraram-se particularmente na avaliação da produção de ERO e no efeito da administração de antioxidantes 7,9,10,18,19 . Deste modo, o presente trabalho caracterizou a condição redox sistémica e peniana em animais diabéticos, num estadio inicial (2 semanas) e avançado (8 semanas) da patologia.…”
Section: Discussionunclassified
“…In addition to medicinal products, nutritional patterns, mostly through the increased ingestion of plant-derived polyphenols, have emerged as an alternative or complementary intervention for the amelioration of MS 5253. Polyphenols are natural antioxidant molecules that are present in food and produce recognized beneficial effects that counteract the increase in oxidative stress, which is strongly associated with MS,255253 intervene in the prevention of CV diseases, significantly reduce mortality that is associated with CV diseases54 and ameliorate erectile function 5556…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of research has indicated that antioxidants can improve ED [7,12,13,14,15]. The purpose of this study was to investigate whether PNS are able to improve the erectile function of rats with DMED and whether the antioxidant effect of PNS underlies this mechanism.…”
Section: Introductionmentioning
confidence: 99%